Sentidos e significados atribuídos às visitas domiciliárias realizadas pelo CRAS - Lauermann, Jusiene Denise (2015)
The present dissertation aims at an analysis of the home visit as a practice of attention and intervention performed by public policies such as health and social care. Therefore, we developed three texts. The first aims to describe and analyze scientific articles that present views of user families of Basic Health Units (BHU) on home visits. The second has as main objective to present a critical reflection on the knowledge and practices triggered during the performance of this practice, trying to demonstrate what the worldview has permeated, especially in the field of psychology. The third, in turn, is meant to analyze how users of a Social Assistance Reference Center (CRAS) have understood the visits in their homes by the professionals of this unit. So, in order to reach the established objectives, we performed two integrative reviews seeking scientific articles in databases and field research that made use of the conversation wheel and the field diary. We begin, therefore, presenting a descriptive systematization and a qualitative analysis of the articles found in one of the reviews. Then we seek, also through a qualitative analysis, observe the predominant worldview in the home visit in articles that discuss this practice in dialogue with psychology. At this point, we took ethics as driving force for critical reflection. Finally, we present the information collected during the field research, showing the understanding of users of a CRAS about the home visit. Through a conversation wheel and the use of field diary was possible to observe and analyze some of the social representations of them about this practice. The analysis of all the material, much of reviews as the information collected in the field, was taken from the Social Representations Theory (SRT) and from the perspective of Critical Social Psychology (PSC). With the analysis, we understand the narratives brought by the articles show that families situate the home visit as a goodness of attitude or obligation of professional, moving antinomies as goodness/badness and good/bad. They also show there are representations of the visits linked to the idea of a meeting between two worlds, the common sense and science, based on some antinomies conceived from a positivist paradigm and a biomedical model. Already with the analysis of field data, we conclude that the professionals, guided by ideas of prevention, promotion and protection, may be making institutional violence masked by a careful conception. It comes to the faint line that daily permeates the practice in this playing field: the close proximity of care and control, autonomy and tutelage, respect for privacy and a permissive posture. The attention, thought and care in the field of social assistance, particularly in the practice of home visits, are not always present. Often there is a concern with change or abandonment of some behavior that prevents an attentive listening or recognition of the Other.